A pilot study examining the efficacy of hochuekkito for improving quality of life in patients with myeloproliferative neoplasms. (14th May 2022) - Edahiro, Yoko; Koike, Michiaki; Nojiri, Shuko; Harada, Yoshinao; Gotoh, Akihiko; Fujibayashi, Kazutoshi; Nishizaki, Yuji; Yanagisawa, Naotake; Takaku, Tomoiku; Nitta, Hideaki; Tsukune, Yutaka; Misawa, Kyohei; et al.
Abstract: Background: The prognosis of Philadelphia chromosome-negative myeloproliferative neoplasms is relatively favorable, but the quality of life can be severely affected by myeloproliferative neoplasm-related symptoms such as fatigue, pruritus, night sweats, bone pain, fever and weight loss. In this study, we administered hochuekkito, a traditional herbal medicine, to patients with myeloproliferative neoplasms and investigated whether there was a reduction in myeloproliferative neoplasm-related symptoms. Methods: We conducted a randomized parallel-group pilot study. Patients were assigned to a hochuekkito administration or non-hochuekkito administration group. Myeloproliferative neoplasm-related symptoms based on Myeloproliferative Neoplasm Symptom Assessment Form total symptom score and European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-Core 30 were examined before hochuekkito administration and 4 and 8 weeks after administration. Results: Among the 42 patients included in the analysis, 21 were assigned to the hochuekkito group and 21 were assigned to the control group. After administering hochuekkito, the median values of Myeloproliferative Neoplasms Symptom Assessment Form total symptom score at 4 and 8 weeks in the hochuekkito group demonstrated a decreasing trend; however, the difference between the two groups was not significant. Conclusions: In this study, we were unable to demonstrate significant differences between the hochuekkito and control groups in terms of the efficacy of hochuekkito in treating myeloproliferative neoplasm-related symptoms. However, there were cases that presented prominent improvement in symptoms in the hochuekkito group. The only reported adverse event was grade 1 impaired hepatic function. Therefore, hochuekkito might be a therapeutic option for patients with severely affected quality of life due to myeloproliferative neoplasm-related symptoms. Abstract : Though hochuekkito did not show superior effect in terms of myeloproliferative neoplasm-related symptoms compared to control groups, there were cases presenting prominent improvement. Therefore, hochuekkito might be a therapeutic option.